Temporal Profiles of P-Tau, T-Tau, and P-Tau:Tau Ratios in Cerebrospinal Fluid and Blood from Moderate-Severe Traumatic Brain Injury Patients and Relationship to 6-12 Month Global Outcomes - Rubenstein, Richard; McQuillan, Leah; Wang, Kevin K W; Robertson, Claudia; Chang, Binggong; Yang, Zhihui; Xu, Haiyan; Williamson, John; Wagner, Amy K (Journal of neurotrauma, 2024)
Traumatic brain injury (TBI) can initiate progressive injury responses, which are linked to increased risk of neurodegenerative diseases known as "tauopathies." Increased post-TBI tau hyperphosphorylation has been reported in brain tissue and biofluids. Acute-to-chronic TBI total (T)-tau and phosphorylated (P)-tau temporal profiles in the cerebrospinal fluid (CSF) and serum and their relationship to global outcome is unknown. Our multi-site longitudinal study examines these concurrent profiles acutely (CSF and serum) and also characterizes the acute- to-chronic serum patterns. Serial serum and CSF samples from individuals with moderate-to-severe TBI were obtained from two cohorts (acute, subacute, and chronic samples from University of Pittsburgh [UPitt] [ 286 unique subjects] and acute samples from Baylor College of Medicine [BCM] [ 114 unique subjects]) and assayed for T-tau and P-tau using the Rolling Circle Amplification-Surround Optical Fiber ImmunoAssay platform. Biokinetic analyses described serum T-tau and P-tau temporal patterns. T-tau and P-tau levels are compared with those in healthy controls ( = 89 for both CSF and serum), and univariate/multivariable associations are made with global outcome, including the Disability Rating Scale (DRS) and the Glasgow Outcome Scale-Extended (GOS-E) scores at 3 and 6 months post-TBI (BCM cohort) and at 6 and 12 months post-TBI (UPitt cohort). For both the UPitt and BCM cohorts, temporal increases in median serum and CSF T-tau and P-tau levels occurred over the first 5 days post-injury, while the initial increases of P-tau:T-tau ratio plateaued by day 4 post-injury (UPitt: = 99, BCM: = 48). Biokinetic analyses with UPitt data showed novel findings that T-tau ( = 74) and P-tau ( = 87) reached delayed maximum levels at 4.5 and 5.1 days, while exhibiting long serum half-lives (152 and 123 days), respectively. The post-TBI rise in acute (days 2-6) serum P-tau (up to 276-fold) far outpaced that of T-tau (7.3-fold), leading to a P-tau:T-tau increase of up to 267-fold, suggesting a shift toward tau hyperphosphorylation. BCM analyses showed that days 0-6 mean CSF T-tau and P-tau levels and P-tau:T-tau ratios were associated with greater disability (DRS) ( = 48) and worse global outcome (GOS-E) ( = 48) 6 months post-injury. Days 0-6 mean serum T-tau, P-tau, and P-tau:T-tau ratio were not associated with outcome in either cohort (UPitt: = 145 [DRS], = 154 [GOS-E], BCM: = 99 [DRS and GOS-E]). UPitt multivariate models showed that higher chronic (months 1-6) mean P-tau levels and P-tau:T-tau ratio, but not T-tau levels, are associated with greater disability (DRS: = 119) and worse global outcomes (GOS-E: = 117) 12 months post-injury. This work shows the potential importance of monitoring post-TBI T-tau and P-tau levels over time. This multi-site longitudinal study features concurrent acute TBI T-tau and P-tau profiles in CSF and serum, and also characterizes acute-to-chronic serum profiles. Longitudinal profiles, along with no temporal concordance between trajectory groups over time, imply a sustained post-TBI shift in tau phosphorylation dynamics that may favor tauopathy development chronically.